PERKAWINAN POLIGAMI DI WILAYAH HUKUM PENGADILAN AGAMA KOTA PADANG (MEKANISIME PEMBERIAN IZIN, DASAR HUKUM, SYARAT-SYARAT POLIGAMI DAN PELAKSANAANYA) - Yohanis, Yohanis (Soumatera Law Review, 2018)
Marriage between a man and a woman is known as monogamous marriage, but there is also a form of marriage known as polygamous marriage. In a polygamous marriage institution a man is bound to marriage with many women as his wife. The Marriage Law provides that a court may grant a husband permission to have more than one wife if desired by the concerned public authorities. This paper is the result of the authors research on licensing and the mechanism of polygamy in the jurisdiction of Religious Courts of Padang City. From the results of research, it can be concluded that the perpetrators of polygamy registered in the Religious Court of Padang City is very little, while the polygamy requirement is the existence of permission from the Religious Courts, the application for permission in the Religious Court of Padang City meets the syarta which has been specified by applicable laws and regulations, which form the basis of judges consideration in deciding cases of polygamy permits, the achievement of justice from polygamy actors, the fulfillment of administrative procedures for the application of polygamy permits, the protection of the interests of each party, the factors of equality and economic factors of the perpetrators polygamy. The judge will accept a polygamy permit application if the basics of the consideration are met.